Efeitos da frutalina (lectina da fruta pão - Artocarpus incisa) durante a maturação e fertilização in vitro de oócitos suínos - Silva, Bianca Régia (2018)
The aim of the present study was to evaluate the effect of frutalin (FTL) on in vitro maturation (IVM), and fertilization (IVF) of porcine oocytes. In the experiment 1, cumulus-oocyte complexes (COCs) were submitted to IVM in maturation medium alone or supplemented with different FTL concentrations (0.6, 6 and 60 μg/mL), or 0.3 μg/mL doxorubicin (DXR). After IVM, some oocytes were evaluated for chromatin configuration, and the remaining oocytes were submitted to in vitro fertilization. In experiment 2, matured oocytes were fertilized in IVF medium alone (control) or in presence of different FTL concentrations (0.6, 6 and 60 μg/mL), or 0.3 μg/mL DXR. After 18 h post fertilization, the endpoints penetration rate, monospermy, spermatozoa per oocyte, and the IVF efficiency were evaluated in both experiments. In experiment 1, 6 and 60 μg/mL FTL, as well as DXR increased (P < 0.05) the rate of oocytes with abnormal chromatin configuration when compared to oocyte matured in control medium alone or supplemented with 0.6 μg/mL FTL. The percentage of meiotic resumption in oocytes cultured with 60 μg/mL FTL or DXR were lower (P < 0.05) than in the other treatments. Moreover, oocytes matured with 6 and 60 μg/mL FTL and DXR showed lower IVM efficiency when compared to those matured with 0.6 μg/mL FTL or in control medium. Exposure of COCs during IVM to 6 or 60 FTL reduced (P < 0.05) penetration and sperm/oocyte rates when compared to other treatments, but IVF efficiency was lower (P < 0.05) than that in control medium alone or with 0.6 μg/mL FTL. In experiment 2, 0.6 μg/mL FTL increased (P < 0.05) monospermy and IVF efficiency rates when compared to control medium. In addition, 6 and 60 μg/mL FTL reduced (P < 0.05) penetration, sperm/oocyte rates and IVF efficiency, although increasing (P < 0.05) monospermy rates. In conclusion, 0.6 μg/mL FTL reduces the penetration rates and the number of sperm/oocytes increasing IVF efficiency without harmful effects. Higher concentrations of FTL have toxic effects during oocyte maturation and reduced IVF efficiency.